IDENTIFICATION AND COMPARATIVE CHARACTERIZATION OF NEW LACTIC ACID BACTERIA ISOLATED FROM ARMENIAN DAIRY PRODUCTS BY PHENOTYPIC AND MOLECULAR METHODS (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
More than 600 strain isolates were obtained from 200 matsun and salted cheeses samples. The strains were screened for potential probiotic properties, antibiotic and phenol resistance. Eight different lactic acid bacteria strains with high antibacterial activities were identified by multiphase approach comprising classical and molecular methods and indicated their relation to four species distributed in two genera Lactobacillus (L. rhamnosus, L. helveticus, L. delbrueckii) and Enterococcus (E. faecium).
Keywords: lactic acid bacteria, PCR identification